The individual and privacy - Cannataci, Joe (The library of essays on law and privacy, 2016)
pt. 1. The time dimension : perspectives from history and anthropology through philosophy to religion and technology law -- pt. 2. The space dimensions in privacy perspectives and methodologies : from early days in sociology through social psychology to the socio-legal approach and the cognitive sciences in the twenty-first century -- pt. 3. The cultural dimension : conceptualizations of privacy and personality around the world.